Human salivary gland stem cells ameliorate hyposalivation of radiation-damaged rat salivary glands - Jeong, Jaemin (Nature Publishing Group, 2013)
Salivary function in mammals may be defective for various reasons, such as aging, Sjogren's syndrome or radiation therapy in head and neck cancer patients. Recently, tissue-specific stem cell therapy has attracted public attention as a next-generation therapeutic reagent. In the present study, we isolated tissue-specific stem cells from the human submandibular salivary gland (hSGSCs). To efficiently isolate and amplify hSGSCs in large amounts, we developed a culture system (lasting 4–5 weeks) without any selection. After five passages, we obtained adherent cells that expressed mesenchymal stem cell surface antigen markers, such as CD44, CD49f, CD90 and CD105, but not the hematopoietic stem cell markers, CD34 and CD45, and that were able to undergo adipogenic, osteogenic and chondrogenic differentiation. In addition, hSGSCs were differentiated into amylase-expressing cells by using a two-step differentiation method. Transplantation of hSGSCs to radiation-damaged rat salivary glands rescued hyposalivation and body weight loss, restored acinar and duct cell structure, and decreased the amount of apoptotic cells. These data suggest that the isolated hSGSCs, which may have characteristics of mesenchymal-like stem cells, could be used as a cell therapy agent for the damaged salivary gland.